Application of Computational Law and Artificial Intelligence Methods for Sharia Compliance Analysis of E-Waste Management Systems Based on Blockchain - Gulyamov, Said (Suhuf: International Journal of Islamic Studies, 2024)
This paper aims to 1) develop a methodology using computational law and blockchain technology to ensure Sharia compliance in e-waste management systems; 2) propose a conceptual model for a Sharia blockchain platform enabling compliance monitoring and verification; and 3) formulate recommendations to facilitate real-world implementation. The study employs a conceptual approach using inductive analysis of Sharia principles, deductive reasoning, and systems modeling to formulate design requirements and components for a blockchain platform that can enable transparent, tamper-proof monitoring and control of e-waste handling in accordance with Islamic law. Firstly, analysis reveals five key criteria for Sharia compliance in e-waste management and how blockchain, smart contracts, and AI can address these. A comprehensive compliance assurance methodology leveraging these technologies is proposed. Secondly, a conceptual model is delineated for a multipurpose Sharia blockchain platform encompassing consensus, cryptography, smart contract rule engines, and AI analytics. Thirdly, recommendations are synthesized covering technological, regulatory, economic, infrastructure, and social factors needed to enable real-world implementation. This pioneering research bridges Sharia law, sustainability, and emerging technologies to offer culturally attuned e-waste management solutions. The methodology, conceptual models, and practical framework devised inform development of next-generation systems for values-aligned compliance assurance, with potential impact extending beyond the realm of e-waste contexts.